Normalisasi Hubungan Israel dan Arab dalam Konteks Israel-Palestina - Anna Zakiah Derajat; Toni Kurniawan (Parahyangan Center for International Studies, 2022)
The normalization of relations between Israel and Arabs in the current decade is one of the obstacles in the struggle for Palestinian independence. In 2020, Donald Trump has mediated between four Arab countries to agree on normalizing relations with Israel. Behind this agreement, there are various interests of related Arab countries, Israel and the US in the Middle East region. This study aims to explain how the normalization of relations between Israel and the Arab state under the Trump administration and its impact on issues in the Middle East region, as well as the struggle for Palestinian independence using a constructivist perspective. The researchmethod used is qualitative research with a literature study approach. Based on the results of data analysis, the normalization of relations between Israel and the Arab state is carried out based on elements of identity, interest, intention, and values, so that the US is considered to play Israel as a political tool in the Middle East. Keywords: Constructivist, Normalization of relationships, Palestinian independence, Donald Trump's political policies, The interest of the 2020 United States presidential election.